A Study on point-to-point protocol in Data Communication and Networking - Saranya, J (International Journal of Computer Sciences and Engineering, 2019)
The Point-to-point protocol is a protocol designed to respond all the Internet protocol and allow IP addresses to be assigned dynamically as well as support authentication of the User. It connects two routers directly without any host or any other networking device in between These point-to-point protocol can control and manage the transfer of data, connection authentication, transmission encryption and compression.